Pulmonary function as a limiting factor of middle-distance race performance - Venckunas, T.; Balsys, D. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: Exercise induced bronchoconstriction (EIB) is common and underdiagnosed phenomenon of yet largely unknown etiology. This study aimed to estimate prevalence of EIB in response to highly demanding skyscraper race and to test its association with race performance and hypothetical predisposing factors. METHODS: Healthy participants (26 males, 8 females; 31.5+/-6.3 years) from mostly running-based amateur sports were measured for forced expiratory volume in first 1 s (FEV1) before and then repeatedly within 10 min after the completion of the 114 m skyscraper upstairs race. Allergy questionnaire (AQUA) data were collected, and postexercise blood lactate was measured. RESULTS: Over 40% of the participants developed >10% decrement in FEV1 shortly after all-out exercise. While EIB response was not associated with questionnaire-based atopic status, training background, gender, age, anthropometrics, pacing and exertion (estimated from the accumulated blood lactate values), participants exhibiting <10% decrement in FEV1 were faster, especially over the later stages of the race. CONCLUSIONS: Nearly every other participant of the skyscraper race develops EIB not associated with training, demographic, anthropometric and atopic status, pacing and exertion (estimated from postexercise blood lactate), but the responders (FEV1 decrement >10%) were slower indicative of poorer fitness due to EIB developing during the exercise already.